Digital Transformation and Social Media as Sales Drivers at CV.Grand Grafika - Tan, Tiam Wi Hendra Wijaya; Elisabeth Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The development of information and communication technology has had a significant impact on the business world. Data were gathered using a variety of research tools, such as questionnaires for respondents, literature reviews, and direct observation The research is quantitative and uses purposive sampling techniques by conducting surveys and distributing questionnaires to a sample of 96 people.. To evaluate the data, multiple linear regression analysis was used. This study employed multiple linear regression analysis to develop and evaluate three hypothese.. From the results of this study, it can be concluded that digital transformation and social media influence the increase in sales in CV.Grand Graphics, where digital transformation affected 12.1% and social media affected 13.3%, as well as the influence of digital and social transformation on increased sales in CVs. Grand Graphics is 2.1%, where other variables affect sales in CV.Grand Grafika is Price and Customer Loyalty.